Outcomes and excess costs among patients with cardiovascular disease - Ademi, Z.; Liew, D.; Zomer, E.; Gorelik, A.; Hollingsworth, B.; Steg, P.; Bhatt, D.; Reid, Christopher (2013)
Objective: To report on two-year cardiovascular (CV) event rates and quantify the cost of cardiovascular disease using the Australian Reduction of Atherothrombosis for Continued Health (REACH) registry. Methods: Prospective registry of 2873 patients with multiple risk factors (MRF), coronary artery disease (CAD), cerebrovascular disease (CerVD) and peripheral artery disease (PAD), recruited through 273 Australian general practitioners. Government reimbursement data from 2011 was used to calculate direct health care costs (pharmaceuticals, outpatient and hospitalisation costs). The main outcome of interest was two-year rates and associated excess costs of cardiovascular death, myocardial infarction, stroke, and hospitalisation for cardiovascular procedures. Results: The two year follow-up data were available for 2856 (99.4%) patients. Incidence of any hospitalisation and cardiovascular death was highest among those with previous history of PAD at baseline 49% (n= 126), and 5.1% (n= 13). Non-fatal cardiovascular events were highest among the PAD and CAD groups (21.8% (n= 56) and 14.1% (n= 297) respectively). Those with previous history of PAD and CerVD at baseline had the highest likelihood of CV death (OR = 2.53 (95% CI: 1.58-4.08) and OR = 1.61 (1.05-2.46) respectively) in comparison to other groups. Patients with PAD had the highest likelihood of vascular interventions OR = 3.11 (95% CI: 2.09-4.63) at two years. Overall, the mean (SD) direct expenditure over two years of follow-up per person was A$7544 (A$10,758). In the adjusted model, patients with CAD and PAD incurred A$1093 (95% CI A$24 - A$2072) and A$4890 (95% CI A$3105 - A$6869) more in mean total costs compared to patients with MRF. Conclusions: Patients with PAD had the highest likelihood of vascular interventions and CV death, and incurred high excess costs in comparison to other groups. © 2013 Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) and the Cardiac Society of Australia and New Zealand (CSANZ).